The Role of a Decision Support System in Back Pain Diagnoses: A Pilot Study. (25th March 2019) - Benditz, Achim; Faber, Florian; Wenk, Gabriela; Fuchs, Tina; Salak, Natalie; Grifka, Joachim; Vogl, Matthias; Menke, Matthias; Jansen, Petra
Abstract : It is the main goal of this study to investigate the concordance of a decision support system and the recommendation of spinal surgeons regarding back pain. 111 patients had to complete the decision support system. Furthermore, their illness was diagnosed by a spinal surgeon. The results showed significant medium relation between the DSS and the diagnosis of the medical doctor. Besides, in almost 50% of the cases the recommendation for the treatment was concordant and overestimation occurred more often than underestimation. The results are discussed in relation to the "symptom checker" literature and the claim of further evaluations.